2010
DOI: 10.1182/blood-2009-08-237537
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab inhibits B-cell receptor signaling

Abstract: Rituximab (RTX),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 44 publications
9
53
1
Order By: Relevance
“…In our study, formation of CLL cell aggregates by CD19 was only reduced by 25% after using protein tyrosine kinase inhibitors, whereas inhibition of F-actin assembly also resulted in a minor inhibitory effect, which is in agreement with previously published results (30). In contrast, the aggregation was completely abrogated by disruption of the cholesterol-rich plasma membrane rafts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, formation of CLL cell aggregates by CD19 was only reduced by 25% after using protein tyrosine kinase inhibitors, whereas inhibition of F-actin assembly also resulted in a minor inhibitory effect, which is in agreement with previously published results (30). In contrast, the aggregation was completely abrogated by disruption of the cholesterol-rich plasma membrane rafts.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies pointed to the possible involvement of CD20 in BCR signaling responses, albeit the in vivo significance of these findings is unclear (30). To further examine the physiological differences between the CD19-R and CD19-N subpopulations, we tested the effects of the anti-CD20 therapeutic Ab rituximab on these cells, both in vitro and in vivo.…”
Section: Cd19-responsive Cll Cells Are Preferentially Eliminated In Vmentioning
confidence: 99%
“…Janas et al [38] have shown that rituximab-induced translocation of CD20 to lipid rafts is crucial for increased intracellular Ca 2+ levels and downstream apoptotic signaling. Also the rituximab binding to CD20 significantly interferes with B-cell receptor (BCR) signaling, resulting in a time-dependent inhibition of the BCR-signaling cascade involving Lyn, Syk, PLCc2, Akt, and ERK, and calcium mobilization [39]. Walsh et al [40] have suggested that after the ligation of CD20 by rituximab, CD20 molecules cluster together and associate with the BCR, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of lipid rafts and their association with CD20 and consequent activation of src kinases are all dependent on cholesterol, with cholesterol depletion inhibiting rituximab-induced apoptosis (14). In follicular lymphoma (FL) cell lines, we found that rituximab inhibits B-cell-receptor signaling by preventing B-cell-receptor relocalization into rafts and decreasing raftassociated cholesterol content (15). CD20 translocation into rafts seems to be necessary for calcium mobilization and for rituximab-induced apoptosis in Burkitt lymphoma cell lines (16).…”
Section: Effects Of Rituximab On Lipids and Raftsmentioning
confidence: 92%